Measuring consumer perception in respiratory mask product based on affective evaluation - Shaari, Nazlina; Lee, Z. N.; Abd Rahman, Khairul Aidil Azlin (RMP Publications, 2018)
Haze has been an annual problem in the Southeast Asian region, especially in Malaysia where its neighbouring country Indonesia’s forest fires are the main cause for this phenomenon. It has caused skies to be obscured, air to be clogged, lowered visibility and most importantly it severely affects humans’ health. The objective of this study is to identify the consumer perception in mask design used during haze. The focused mainly on using the affective data to redesign the mask products. The online questionnaires about the awareness of the public regarding haze, positive and negative reviews of different types of respiratory masks were randomly sent to respondents. The data was then analyzed quantitatively using affective evaluation. Results showed the most commonly used product against haze were surgical masks and the N95. However many were reluctant users of the masks as they were uncomfortable. Results also showed that masks had to have ergonomic features to provide comfort and supported the view that the current respiratory mask designs had to be more aesthetic as well.